Evaluation of Caries Removal Using Carie-Care and SmartPrep Burs in Primary Teeth: A Comparative Study - Royasa Shakya; Bandana Koirala; Mamta Dali; Sneha Shrestha; Gajendra Birajee (Journal of South Asian Association of Pediatric Dentistry)
Background: As the importance of preserving natural teeth becomes evident, the notion of minimal intervention dentistry (MID) is becoming more acceptable. Two such feasible techniques for caries removal are chemomechanical agents (Carie-Care) and polymer burs (SmartPrep bur). Aim: To compare the clinical efficacy (effectiveness) and efficiency (time taken) of selective removal of carious dentin using Carie-Care and SmartPrep burs in primary teeth. Materials and methods: A comparative split-mouth study was carried out on 4–9-year-old children. Around 70 primary second molars in 35 children were allocated to group C (Carie-Care) and group S (SmartPrep burs). Efficacy and efficiency of caries removal, behavioral change, and pain perceived were evaluated in both groups. Results: The efficacy of caries removal was better with Carie-Care than SmartPrep burs when assessed using visual, tactile, and caries-detector dye methods, though not statistically significant. However, significantly more time was taken for caries removal with Carie-Care than SmartPrep burs (p < 0.001). There was also a statistically significant positive change in behavior in group C and group S when assessed using the Frankl scale (p < 0.001 and p = 0.004) and the Venham scale (p < 0.001 and p = 0.002), respectively. Additionally, 91.4% in group C and 77.1% in group S demonstrated comfort during caries removal, which was statistically nonsignificant (p = 0.101). Conclusion: Carie-Care and SmartPrep burs were both equally effective and comfortable and brought about a positive behavior change, though Carie-Care was found to be more time-consuming. Clinical significance: Minimal intervention techniques for caries removal maximize the preservation of healthy dental tissues while reducing dental fear and anxiety (DFA) in children.